2020
DOI: 10.1038/s41598-020-74928-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction behavior of chromium(VI) with oxalic acid in aqueous solution

Abstract: The direct Cr(VI) reduction process by oxalic acid was conducted. The existence of Cr(VI) in the reaction medium was measured by software Visual MINTEQ and the concentration of Cr(VI) was measured by ICP-OES. The results showed that the Cr(VI) was efficiently reduced by oxalic acid at high reaction temperature and high dosage of oxalic acid. The reduced product, Cr(III), was easily generated stable complex compounds (Cr(HC2O4)3) with oxalate, which displayed a negative effect on the reduction process. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…The analysis of variance of the reduction efficiency of Cr (VI) is shown in Table 2. The results show that the p-value of the model was <0.0001, which indicates that the selected model was significant and suitable for simulating the reduction process of Cr (VI) [21,30]…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The analysis of variance of the reduction efficiency of Cr (VI) is shown in Table 2. The results show that the p-value of the model was <0.0001, which indicates that the selected model was significant and suitable for simulating the reduction process of Cr (VI) [21,30]…”
Section: Resultsmentioning
confidence: 93%
“…A recent study indicated that Cr (VI) is easily reduced to Cr (III) in a strong acidic medium [12,13,21]. A series of experiments were conducted with the concentration of H 2 SO 4 ranging from 0 to 20 g/L at various dosages of biochar.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations